Desenvolvimento de matriz 3D a base de quitosana, gelatina econdroitina como suporte para osteogênese de células-tronco derivadasdo tecido adiposo e sua aplicação em Engenharia de Tecido ósseo - Luiza Rachel Pinheiro de Carvalho (2012)
he reconstruction of major bone segments remains a significant clinical problem. The clinical and economic impacts of the bone defect treatments are amazing. The currently available therapeutic approaches include transplant grafts or different synthetic biomaterials implants, but none has proved to be entirely satisfactory. Tissue Engineering provides a promising alternative for the repair of lesions in the bone tissuecaused by trauma or associated with aging such as osteoporosis. The purpose of this new field of regenerative medicine is to combine cell, scaffold and bioactive agents for the regeneration of a new functional tissue. The 3D porous structures are used as models for the temporary cell seeding, migration, proliferation and differentiation of the tissueprior to regeneration or biologically functional natural extracellular matrix. In the field of orthopedics, the use of bioabsorbable implants is becoming more common. These arrays must be porous extracellular matrix (ECM), resemble the native tissue, and be biocompatible and biodegradable. Chitosan, in combination with gelatin andchondroitin, meets the basic needs for the choice of the constituent polymer matrix. The decision of the cell type is particularly important in the development of tissue engineering. Stem cells derived from adipose tissue (ADSC) appear to be an ideal candidate for this technique, since it presents the potential for self and multilinhage. Based on this principle, this study aimed to develop and characterize 3D matrices of chitosan, gelatin and chondroitin, and assessing response in vitro and in vivo of ADSC osteogenesis in these scaffolds. The 3D matrix of this study was highly porous, having interconnected pores. When osteogenesis is induced, in 2D and 3D culture, the ADSC began to express specific markers of osteogenic cells. In cultivation in 3D matrix, ADSC were capable of cell adhesion and interconnectivity, as well as having theirproliferation, viability and increased osteogenesis, as demonstrated by the results of MTT assay, FA, measurement of collagen and staining of mineralized structures. Through analysis of the ectopic site implants and implants in rat calvarias lesions in vivo, it was possible to show that the 3D matrix did not induce a strong inflammatory response and did not affect the function of the implanted tissue. The matrix was shownto be biocompatible and biodegradable, and allows the implant angiogenesis. When colonized by ADSC, the implants had an early angiogenesis and a mature osteogenesis. Furthermore, ADSC-EGFP were inserted into the newly formed ECM and visualized. Thus, 3D matrices developed in this study showed promise for bone tissue engineering and it is biocompatible, biodegradable and provides a good environment for the cell attachment and proliferation, angiogenesis and osteogenesis. The union of the data obtained for this work allows us to glimpse the possibility of using the 3D matrix of chitosan, gelatin and chondroitin as a potential carrier for mesenchymal stem cells inbone tissue engineering. Thus, our study opens a perspective for clinical application and for future studies for the reconstruction of tissues